2019
DOI: 10.1037/ocp0000158
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic stress disorder symptoms and sleep in the daily lives of World Trade Center responders.

Abstract: Sleep disturbances are common in posttraumatic stress disorder (PTSD) and can have major impacts on workplace performance and functioning. Although effects between PTSD and sleep broadly have been documented, little work has tested their day-to-day temporal relationship particularly in those exposed to occupational trauma. The present study examined daily, bidirectional associations between PTSD symptoms and self-reported sleep duration and quality in World Trade Center (WTC) responders oversampled for PTSD. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 133 publications
4
41
0
Order By: Relevance
“…Specifically, shorter sleep duration, more trouble falling asleep, and more difficulty staying asleep the previous night predicted higher PTSS the following day and more difficulty staying asleep on average predicted higher PTSS. Our initial analyses examined each sleep characteristic in a separate single predictor model similar to those used by Short et al [38] and Dietch et al [37]. We found previous night's sleep duration, sleep quality, trouble falling asleep, and difficulty staying asleep predicted next day PTSS.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Specifically, shorter sleep duration, more trouble falling asleep, and more difficulty staying asleep the previous night predicted higher PTSS the following day and more difficulty staying asleep on average predicted higher PTSS. Our initial analyses examined each sleep characteristic in a separate single predictor model similar to those used by Short et al [38] and Dietch et al [37]. We found previous night's sleep duration, sleep quality, trouble falling asleep, and difficulty staying asleep predicted next day PTSS.…”
Section: Discussionmentioning
confidence: 99%
“…Findings from the prior studies are not consistent and do not provide a clear understanding of the relationship between previous night's sleep disturbance and next day's PTSS; Short et al [38] found sleep efficiency and quality but not duration or nightmares predict PTSS and Dietch et al [37] found sleep duration but not quality predict PTSS. Thus, additional research is needed to understand the temporal relationship between previous night's sleep disturbance and PTSS the following day.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Data from the Workplace Bullying and Harassment cohort in Denmark also found evidence for a reciprocal association [75]. A small reverse effect, with reduced sleep duration (but not sleep quality) predicting increased post-traumatic stress, was also observed in World Trade Center (WTC) responders [76].…”
Section: Discussionmentioning
confidence: 99%